Analysis of Context-Specific Mental Health Factors of Construction Workers in Indonesia - Hansen, Seng; Fassa, Ferdinand; Pastika, Nathania Sasi (Universitas Airlangga, 2025)
Introduction: The construction industry is widely recognized as one of the sectors with significant mental health challenges. Many studies revealed that mental health problems such as depression, burnout, and sleep difficulty are more common in the construction industry compared to other industries. The causes may include high risk environment, long working hours, job insecurity, and machoism culture. On the other hand, the issue of mental health in the Indonesian construction sector is still not widely understood. Hence, this study investigates the key context-specific factors that influence the mental health of construction workers. Method: A mixed-method approach was employed, consisting of an integrative literature review (ILR) and exploratory factor analysis (EFA). The ILR identified twenty-three context-specific mental health factors, subsequently used as input in the questionnaire survey. The questionnaire consists of demographic characteristics and measurement of mental health factors using a six-point Likert scale. The survey was distributed to construction workers in Indonesia, each with a minimum of two years of work experience. The collected data were analyzed using EFA. Result: This study found five key groups of context-specific factors: workplace, work pressure, role, gender inequality, and psychosocial factors. These factors are found to be deeply interconnected, often exacerbating one another. The study underscores the complexity of mental health issues in this high-pressure, high-risk industry. The results suggest that addressing these challenges requires a multifaceted approach to better understand and alleviate the stress experienced by construction workers. Conclusion: This study presents five mental health determinants among construction workers in Indonesia. The findings can form the basis for further research and the formulation of work policies that are more responsive to local conditions.